Ecclesiastical Terminology in TÖRE BITIGI: ARÏ - Erk, Kutluay (Acta Orientalia Vilnensia, 2017)
In this article the semantic field of the Armeno-Kipchak word arï/ari “holy, sacred” is examined on the basis of Töre Bitigi (Wrocław version), which is an Armeno-Kipchak version of the Old Armenian law code Datastanagirk’. This magistrative-juridical text was based in a large part on ecclesiastical prescriptions. Accordingly it is possible to see a group of religious terms in the text and the word of arï/ari is one of them. This significant term shows parallelism with other historical Turkic texts, which have been translated from the Holy Book. Daγï da ne üčün emdi klädik yazmaga törälärni, ya ne säbäptän teprändi esimiz bu iškä [...] bu vaχtlarda erinčekliktän üvrämägä klämäslär Eski u Yäŋï Törälärni ne markarẹlardan, ne Awedarandan, ki bolgaylar edi ari bitiklerniŋ küčündän bilmägä könü töräni. Anïŋ üčün klädik bu Törä bitiki bilä oyatmaga alarnï, nečik kimsäni yuχudan. Töre Bitigi/Ekinči, ne üčün yazdïq ya kimniŋ pričinasïndan 5r/160r